Resveratrol treatment reveals a novel role for HMGB1 in regulation of the type 1 interferon response in dengue virus infection - Zainal, N.; Chang, C.P.; Cheng, Y.L.; Wu, Y.W.; Anderson, R.; Wan, S.W.; Chen, C.L.; Ho, T.S.; AbuBakar, Sazaly; Lin, Y.S. (Nature Publishing Group, 2017)
Dengue is one of the most significant mosquito-borne virus diseases worldwide, particularly in tropical and subtropical regions. This study sought to examine the antiviral activity of resveratrol (RESV), a phytoalexin secreted naturally by plants, against dengue virus (DENV) infection. Our data showed that RESV inhibits the translocation of high mobility group box 1 (HMGB1), a DNA binding protein that normally resides in the nucleus, into the cytoplasm and extracellular milieu. HMGB1 migrates out of the nucleus during DENV infection. This migration is inhibited by RESV treatment and is mediated by induction of Sirt1 which leads to the retention of HMGB1 in the nucleus and consequently helps in the increased production of interferon-stimulated genes (ISGs). Nuclear HMGB1 was found to bind to the promoter region of the ISG and positively regulated the expression of ISG. The enhanced transcription of ISGs by nuclear HMGB1 thus contributes to the antiviral activity of RESV against DENV. To the best of our knowledge, this is the first report to demonstrate that RESV antagonizes DENV replication and that nuclear HMGB1 plays a role in regulating ISG production.